Competitive Cities for Jobs and Growth : What, Who, and How - World Bank Group (World Bank, Washington, DC, 2015)
A competitive city is a city that successfully facilitates its firms and industries to create jobs, raise productivity, and increase the incomes of citizens over time. Worldwide, improving the competitiveness of cities is a pathway to eliminating extreme poverty and to promoting shared prosperity. The primary source of job creation has been the growth of private sector firms, which have typically accounted for around 75 percent of job creation. Thus city leaders need to be familiar with the factors that help to attract, to retain, and to expand the private sector. This document aims to analyze what makes a city competitive and how more cities can become competitive.